Efektivitas Pemberian Video Health Education Dan Leaflet Terhadap Pengetahuan Ibu Hamil Tentang Personal Hygiene - Wahyuni, Nur Ismi; SR, Nurqalbi (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Pregnancy is a process that involves various hormones in the body. Personal hygiene in pregnant women is influenced by several factors, one of which is knowledge. Knowledge of personal hygiene for pregnant women is very important because good knowledge can improve the health of pregnant women themselves. This research aims to determine the effectiveness of providing health education videos and leaflets on pregnant women's knowledge about personal hygiene. The type of research used is experimental research with the experimental method used, namely Quasi Experimental, with a